Cloud resources on theory and methods of fuzzy sets and fuzzy logic - N. A. Antipova; O. I. Kulagin (Academy of Cognitive and Natural Sciences, 2014)
The research aims to explore the resources of informational and educational nature available on the Internet and related to the theory of fuzzy logic, implementation of its mechanisms and its application to solving practical problems, the task is examine the opportunity of resources use in teaching of the relevant disciplines in higher educational establishments, the object - the cloud resource tools to support mathematical research, the subject - the cloud resources on the theory and methods of fuzzy sets and fuzzy logic, the main research method - a theoretical study. Methodological and theoretical materials with demonstrative Web-services dedicated to specified topics were found and combined into a single unit. As a result, it was formed a set of training resources that can have a positive effect during its implementation into the process of distance learning.